PENGARUH UKURAN BIJI JARAK PAGAR TERHADAP LAMANYA NYALA API DAN TEMPERATUR YANG DIHASILKAN PADA KOMPOR - Mila, Andika Nopriansyah; Junaidi, Ahmad; Arnoldi, Dwi; Witjahjo, Soegeng; Hidayati, Baiti; Rizal, Syamsul; Medi, Ali (Politeknik Negeri Sriwijaya, Indonesia, 2023)
The availability of fuels, especially fossil fuels, is increasingly scarce, concerns about meeting energy needs in the future are increasing. In urban areas, fuel gas (LPG) is generally used for daily cooking, while in rural areas, kerosene is more commonly used. This significant oil content opens up the possibility to use castor beans as fuel directly. Therefore, in this study the author conducted an experiment entitled